Operationalizing Ocean Health: Toward Integrated Research on Ocean Health and Recovery to Achieve Ocean Sustainability - Andrea Franke; Thorsten Blenckner; Carlos M. Duarte; Konrad Ott; Lora E. Fleming; Antia Avan; Thorsten B.H. Reusch; Christine Bertram; Jonas Hein; Ulrike Kronfeld-Goharani; Jan Dierking; Annegret Kuhn; et al. (One Earth, 2020)
Protecting the ocean has become a major goal of international policy as human activities increasingly endanger the integrity of the ocean ecosystem, often summarized as “ocean health.” By and large, efforts to protect the ocean have failed because, among other things, (1) the underlying socio-ecological pathways have not been properly considered, and (2) the concept of ocean health has been ill defined. Collectively, this prevents an adequate societal response as to how ocean ecosystems and their vital functions for human societies can be protected and restored. We review the confusion surrounding the term “ocean health” and suggest an operational ocean-health framework in line with the concept of strong sustainability. Given the accelerating degeneration of marine ecosystems, the restoration of regional ocean health will be of increasing importance. Our advocated transdisciplinary and multi-actor framework can help to advance the implementation of more active measures to restore ocean health and safeguard human health and well-being.
Keywords: 330